An in-module work practice strategy for vocationally oriented construction degree programmes: the case of the multidisciplinary project - Keraminiyage, Kaushal (International Journal of Strategic Property Management, 2013)
Students who are enrolled in vocationally oriented construction degree programmes can immensely benefit from work practice arrangements. Traditionally such work practice arrangements are organised as a “placement year” during or immediately after the degree programme. Further, these arrangements are often “work place based” practice arrangements requiring students to be based at the work place during the practice period. This system has some significant issues, especially when considering how and when the “learning” takes place. “Multi-disciplinary project” is a module designed to be a part of a vocationally oriented, combined construction undergraduate programme at the University of Salford, United Kingdom, aiming to overcome the issues of work place based work practice arrangements. As a part of this paper, pedagogical principles behind the module design are evaluated based on current literature, examining how previous research have informed the design of this module. Issues encountered during the delivery of the module are also discussed within this paper, based on the unstructured data collected while responding to student inquires and through observations. Nature of those issues are analysed by revisiting current literature, and possible solutions are discussed based on the findings of some of the previous research projects.First Publish Online: 27 Jun 2013